Perceptions amongst medication users regarding South African patient package inserts (PPIs) of scheduled and over-the-counter (OTC) medications - Daleen Krige; Johann Cornelius de Wet (Communicare)
This article reports on the PPI itself, its information, and language usage in the texts, as tested in focus-group sessions, using content analysis. Quantitative readability assessments of selected PPIs revealed that the texts were mostly “difficult” or “very difficult”. However, readability relies not only on text variables, but also on interaction between reader and text. From the findings, certain recommendations are suggested to enhance the reader accessibility and cultural competence of such documents. If PPIs, as a health communication tool, can be seen to be valuable and easily comprehensible sources of medication information, they can fulfil a necessary role in health literacy, especially in a multicultural, developing country such as South Africa, one typified by huge class differences and where more than two-thirds of its households fall within the lower- to middle-income groups.